Ibn Taymiyyah’s “Mardin Fatwa” and the Mongols: An Analysis (KEMANUSIAAN The Asian Journal of Humanities, 2022)
The so-called “Mardin Fatwa” is Ibn Taymiyyah’s (d. 728/1328) description of Mardin city’s status as an Islamic state and its Islamic population. Yahya Michot (b. 1952) and ‘Abd Allah Bayyah’s (b. 1935) modern day readings of this fatwa emphasise different attitudes towards Mongols: Michot emphasised the word yuq?tal (should be fought) in his reading of the text while Bayyah emphasised the word yu’?mal (should be justly treated). This seemingly small difference has had a large impact on Muslims’ understanding of fatwa. For instance, these two readings might alter readers’ perceptions of fatwa as either a literal or metaphorical spiritual battle. This article is grounded in a multidisciplinary approach that combines the selection, translation and critical reading of the selected sources with historical research. The overall approach followed in this article is best described as inductive. This article analyses Michot and Bayyah’s readings through a close reading of the fatwa itself. It concludes by deducing that the Mardin Fatwa text really does represent Ibn Taymiyyah’s opinion and that Yahya Michot’s reading of the text is the correct one.